1992
DOI: 10.1161/01.hyp.19.2_suppl.ii279
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypertension induces disturbances of renal autoregulation.

Abstract: To study if the severity of hypertension could be associated with disturbances of the autoregulation of renal blood flow and glomerular filtration, we compared the renal hemodynamic and functional responses to acute blood pressure reductions of a group of patients with moderate essential hypertension (n=10) with those of a group of patients with severe hypertension (n=10). Blood pressure was reduced to normal levels by a stepwise infusion of sodium nitroprusside, and effective renal blood flow (by 131 I-hippur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…There is evidence that in severe hypertensive patients, the elevated levels of blood pressure induce a displacement of the normal renal auto-regulation curve to the right. Almeida et al [21] reported that although patients with severe hypertension can preserve the auto-regulatory capacity in the hypertensive range of arterial pressure, they showed substantial reductions of effective renal plasma flow during acute normalization of blood pressure. These reductions were accompanied by decreases of a similar magnitude in glomerular filtration.…”
Section: Renal Blood Flow Autoregulationmentioning
confidence: 99%
“…There is evidence that in severe hypertensive patients, the elevated levels of blood pressure induce a displacement of the normal renal auto-regulation curve to the right. Almeida et al [21] reported that although patients with severe hypertension can preserve the auto-regulatory capacity in the hypertensive range of arterial pressure, they showed substantial reductions of effective renal plasma flow during acute normalization of blood pressure. These reductions were accompanied by decreases of a similar magnitude in glomerular filtration.…”
Section: Renal Blood Flow Autoregulationmentioning
confidence: 99%
“…Medullary blood flow, renal interstitial hydrostatic pressure and renal autacoids as angiotensins, kinins, prostaglandins and nitric oxide play an important regulatory role in the regulation of pressurenatriuresis [22][23][24]. Animal models and clinical studies of primary and secondary hypertensive states have been shown an alteration of the renal perfusion pressure-sodium excretion control mechanism, which means that an excessive increase of blood pressure is necessary to trigger the natriuresis in these situations [22,25,26].…”
Section: Basic Science Studiesmentioning
confidence: 99%
“…It is a protective mechanism that maintains nephron function within a narrow range even in the presence of significant blood pressure variation [25,26]. It is a protective mechanism that maintains nephron function within a narrow range even in the presence of significant blood pressure variation [25,26].…”
Section: Basic Science Studiesmentioning
confidence: 99%
“…However, in the presence of diabetes, hypertension, or reduced renal mass, autoregulation of RBF is impaired. [19][20][21] Consequently, if systemic blood pressure decreases, the afferent arteriole cannot dilate appropriately, leading to an acute decline in GFR. In addition, patients with chronic renal disease have limited ability to abruptly curtail sodium excretion in the face of extrarenalvolumedepletion,thuspotentially exacerbating the salt loss.…”
Section: Volume Depletionmentioning
confidence: 99%
“…Renal parenchymal disease is the most common cause of malignant hypertension 34 and a further acute chronic decline in renal function can occur because of myointimal proliferation and fibrinoid necrosis of the renal vascular bed. 34 Although reduction of blood pressure in these circumstances often causes a further transient decline in renal function attributable to impaired autoregulation of RBF, [19][20][21] continued good blood pressure control can improve renal function in the long-term. 35 In fact, some patients who require dialytic support have been able to discontinue dialysis with adequate blood pressure control.…”
Section: Accelerated Hypertensionmentioning
confidence: 99%